RELATIONSHIP BETWEEN FAMILY SUPPORT AND PATIENT COMPLIANCE LEVEL IN CARE FOR DIABETES MELLITUS WOUNDS IN A DIABETES MELLITUS SPECIALIST WOUND CARE HOME IN MALANG CITY - Ramadhanti, Windy Tiara; Supono, Supono; Setyarini, Anggun; Diah Ciptaning Tyas, Maria (Indonesian Journal of Applied Health, 2025)
Non-compliance in caring for diabetic wounds can affect the length of the wound healing process in diabetic patients, lack of family support is thought to be the cause of patient non-compliance in carrying out diabetes mellitus wound care. The purpose of this study was to analyze the relationship between family support and the level of patient compliance in caring for diabetes mellitus wounds at RUMAT Malang City. This research design uses a correlation method with a cross-sectional research design. The population in this study were patients with diabetes mellitus wounds and were undergoing treatment at RUMAT Malang City with a total of 74 patients in the last 3 months. The sampling technique used purposive sampling technique with a sample of 42 people. Statistical test using Spearman test. The results of this study showed that 32 respondents (76.25) had good family support, and 27 respondents (64.3%) were compliant in caring for DM wounds. The results of the spearman test obtained a p-value of 0.000 which means that there is a relationship between family support and the level of patient compliance in caring for diabetes mellitus wounds at RUMAT Malang City. The patient’s family is expected to realize the importance of family support in ensuring patient compliance with wound care. This study is expected to be the basis for developing further research using factors that affect patient compliance in treating diabetes mellitus wounds .